Preserving Kerinci Culture Through Tourists' Purchase Intention for Incoang Batik - Gampo Haryono; Reggyant Abel Frisya; Melifia Liantifa; Rio Baviga (Journal of Sustainable Tourism and Entrepreneurship, 2026)
Purpose: This study aims to examine the influence of cultural values, local wisdom, and marketing strategies on tourists’ purchase intention toward Incoang Batik souvenirs in Sungai Penuh, as well as the role of Incoang Batik in preserving Kerinci cultural identity and the traditional Incoang script. Methodology: This study employed a quantitative explanatory research approach using survey methods through questionnaire distribution to tourists and consumers who had seen, recognized, or purchased Incoang Batik in Sungai Penuh. The independent variables were cultural values, local wisdom, and marketing strategy, while the dependent variable was tourists’ purchase intention. Results: The findings revealed that cultural values had a positive and significant influence on tourists’ purchase intention toward Incoang Batik souvenirs in Sungai Penuh. In contrast, local wisdom and marketing strategy showed no significant influence. However, simultaneously, all three variables significantly affected tourists’ purchase intention, contributing 10.4% to its variance. Conclusions: The study concludes that cultural values constitute the most influential factor in increasing tourists’ purchase intention toward Incoang Batik souvenirs. Limitations: In addition, the research relied on questionnaire-based responses and employed a quantitative approach that could not deeply explore tourists’ cultural interpretations and experiences of Incoang Batik. Contributions: This study contributes to the development of cultural tourism and the creative economy literature by integrating cultural values, local wisdom, and marketing strategy into one research model.